Optimizing Vitamin D Levels: A Real-World Analysis of Supplementation Efficacy and Patient Outcomes - Issa Rasheed Fetian; Brida Caviezel; Laura Szczypior; Eleni Sourla; Titus Baston; Anja Kuzmitski; Kathrin Peschke; Lukas Villiger (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses, 2025)
# Background Vitamin D plays a crucial role in numerous metabolic processes and is essential for overall health. Clinical conditions, ideal threshold values and optimal dose of supplementation remain a topic of discussion. This study presents a real-world analysis of Vitamin D optimization in a diverse patient population.